Prevalence and Clinical Outcome of Philadelphia-Like Acute Lymphoblastic Leukemia: Systematic Review and Meta-analysis - Weerapat Owattanapanich (2020)
© 2019 The Author(s) Background: The presence of Philadelphia (Ph)-like ALL among patients with acute lymphoblastic leukemia (ALL) may indicate a poor prognosis similar to Ph+ ALL, although the data are still inconclusive and the prevalence of Ph-like ALL varied considerably across studies. Patients and Methods: We performed a systematic review and meta-analysis in order to identify all cohort studies of patients with ALL that reported the prevalence of Ph-like ALL and to summarize their results together. The pooled prevalence and rate were calculated by the DerSimonian-Laird random-effect model with double arcsine transformation. Results: Across the 15 included studies describing 11,040 ALL patients, the peak prevalence of the presence of Ph-like ALL among patients with ALL was between ages 11 and 40 years, where the pooled prevalence was 25.8% to 26.2%. The pooled 5-year overall survival rate of Ph-like ALL was 42.8% (95% confidence interval, 23.9-64.1; I2 93%). Comparative analysis with B-other ALL patients was conducted by the Mantel-Haenszel method; it found that Ph-like ALL patients had a significantly lower chance of being alive at 5 years (pooled odds ratio, 0.35; 95% confidence interval, 0.25-0.50; P < .00001, I2 = 40%). The chance of Ph-like ALL patients surviving at 5 years was similar to Ph-positive ALL patients (pooled odds ratio, 0.72; 95% confidence interval, 0.26-2.02; P = .53, I2 = 77%). Conclusion: Ph-like ALL is not uncommon among ALL patients, and its presence is associated with an unfavorable outcome. More investigations are needed for better therapeutic options. Philadelphia (Ph)-like acute lymphoblastic leukemia (ALL) has disease phenotypes similar to Ph+ ALL. This meta-analysis aimed to include cohort study of patients with ALL who reported the prevalence of Ph-like ALL. Across the 15 included studies, the most common gene subgroup was CRLF2 gene rearrangement, and the peak prevalence of Ph-like ALL occurred in adolescents and young adults.